Sie sind auf Seite 1von 4

# International Journal of Basic & Applied Sciences IJBAS-IJENS Vol:12 No:06 49

## The Construction of Regular Semigroups With

Medial Idempotent
O. Hysa

Abstract M. Loganathan (1987) has constructed an where a, b E(S) such that a xfhy b in S, is semigroup.
semigroup W W ( E, S ) in terms of idempotent-generated Proposition II: If (Re , x, Lf) W and x2 = x, then,
regular semigroup E , with a medial idempotent u, and of the (Rex, x , Lxf ) W and (Rex, x , Lxf ) = (Re , x, Lf)
orthodox semigroups with identity S , such that
Proof: Since (Re , x, Lf) W we have ue = xx, fu = xx for
E (S ) u E u. In that paper M. Loganathan has also shown, some x V(x). Then,
that every regular semigroup S with a medial idempotent u, uex = xxx = x = xx and xfu = xxx = x = xx,
can be described in terms of the subsemigroup of S generated
where x V(x). On the other hand ex = exu E u and
by the set of idempotents E E (S ) and the orthodox
xf = uxf u E . So, (Rex, x , Lxf ) W. Since uex = x, we have
subsemigroup of S with identity, uSu . In this paper we will
uex x xx or uex ue or euex eue or ex e that
prove that W W ( E , S ) constructed by Loganathan is
means Rex = Re and dually Lf = Lxf . Hence,
regular semigroup with a medial idempotent. (Rex, x , Lxf ) = (Re , x, Lf).

## Index Term medial idempotent, orthodox semigroup, II. T HE MAIN T HEOREM

Regular semigroup Theorem:
(I) W - is regular semigroup.
I. SOME P RELIMINARES
Definition I: An idempotent u of the regular semigroup S is (II) E (W ) ={(Re, x, Lf) W | LfRe V(x) and x 2 x }
called medial if x E (S ), xux x (III) E (W ) = {( Re , x, L f ) W | x 2 x }
In [4] we have proved this proposition: (IV) u ( Ru , u, Lu ) is medial idempotent in W
Proposition I: If S is regular semigroup that contains a medial
(V) E (W ) E and uW u S
idempotent u, then uS, Su, and uSu are orthodox
semigroups such that: Proof:
(I) Let (Re , x, Lf)W and xV(x) such that xx =
E(uS) = u E = uE, E(Su) = E u = Eu, E(uSu) = u E u = uEu ue and xx = fu. So we have:
and for any x E , we have xux = xx and xux = xx ufu = uxx = xx, ueu = xxu = xx, where xV( x ) and
Let E be an idempotent-generated regular semigroup with a fu Eu , ue uE . Hence, (Rfu, x, Lue) W
medial idempotent u and S let be an orthodox semigroup with We see also that:
identity whose band of idempotents E(S) u E u. From this (Re , x, Lf)(Rfu, x,Lue )(Re , x, Lf) = (Rea, xffux, Lbue )(Re , x,Lf) =
isomorphism we will identify the structures E(S) and u E u. (Rea, xx,Lbue )(Re , x, Lf) =Reac , xxbueex, Ldf) =(Reac ,xxbx, Ldf)
So, as we have shown in [4], u becomes the identity element
of semigroup S. After this, in [4], we considered: and now we must show that (Reac , xxbx, Ldf) = (Re , x, Lf). But
(Rea, xx,Lbue )W means bue u = (xx)(xx) for some inverse
E u/ = {Re| e E u } the set of - classes in E u, (xx) of (xx), or
u E /= {L f | f u E }the set of - classes in u E . xxbueu = xx xxbxxu = xx xxbxxux = xxx
xxbx = x
and we have shown that the set:
So, the middle component is the same, and remains to show
W = { (R e ,x, L f ) E u / x S x u E / | there exists that (Reac , x, Ldf) = (Re , x, Lf). Since (Reac , x, Ldf) W , will exist
x` V(x), ue = xx` and fu = x`x }
x V(x) such that ueac = xx and dfu = xx or
where e E u and f u E , with the binary operation: eac = exx and df = xxf . On the other hand
(R e , x, L f )(R h , y, L k ) = (R ea , xfhy, L bk )
xx E(S) = u E u E u and xx E(S) = u E u E u,
moreover we have:

## 123906-8585- IJBAS-IJENS @ December 2012 IJENS IJENS

International Journal of Basic & Applied Sciences IJBAS-IJENS Vol:12 No:06 50

xx=( xxx)x=(xx )(xx ) and xx=(xxx)x = (xx )(xx ) fu = xx fuf = xxf f = xxf
from which follows xx xx in E u . But, so we have:
fe = xxfexx = x(xfex)x=xxx= x
e E u exx exx eue eac e eac So, fe = x, i.e. fe V(x). We see also that:
Re = Reac in E u. Similarly we will have Lf = Ldf in u E . So, we fe uE Eu uEu E(S ) , hence fe=x is idempotent in
have shown that: S, and since S is orthodox semigroup we have: x = xxx =
(Re , x, Lf) (Rfu, x, Lue ) (Re , x, Lf) = (Re , x, Lf). (*) = xx xx E(S), hence x is idempotent and so, x2 = x. While,
We see also that: to show that LfRe V(x), let be gh LfRe where gLf and

(Rfu, x, Lue )(Re , x, Lf)(Rfu, x, Lue ) = (Rfua, xueex, Lbue )(Rfu, x, Lue ) hRe . So, Lg = Lf in uE and Rh = Re in Eu , that means
= (Rfa, xuex, Lbe )(Rfu, x, Lue ) = (Rfa, xx, Lbe )(Rfu, x, Lue ) = (Rh, x, Lg) = (Re , x, Lf) and this element is idempotent in W,
(Rfac , xxbefux, Ldue ) = (Rfac , xxbex, Lde ) hence ghV(x). So, we have show that LfRe V(x),
where a, b, c, d are idempotents in S. So, consequently:
E(W) { (Re , x, Lf)| LfRe V(x) and x2 = x }
a, b, c, d E (S ) uEu and Let be now (Re , x, Lf)W an element such that LfRe V(x)
a xueex b and c xxbefuxd and x2 = x. We must show that (Re , x, Lf)2 = (Re , x, Lf). By
or definition of the binary operation in W, we have:
a xx b and c xxbexd (Re , x, Lf) (Re , x, Lf) = (Rea, xfex, Lbf) where a,b E(S) = uEu
Now let show that: (Rfac , xxbex, Lde ) = (Rfu, x, Lue ) and a xfex b in S.
Firstly, since (Rfa, xx, Lbe ) W we will have: First, LfRe V(x) feV(x), hence xfex = x. Second, x2 = x
ufa = (xx)(xx) and beu = (xx)(xx) where (xx) V(xx) and by the Proposition II we have:
or ufaxx = xx and xxbeu = xx or fax = x and xbe = x x2 = x (Re , x, Lf) = (Rex , x, Lxf). So, Re = Rex
From xbe = x it follows xxbex = xxx or xxbex = x, which or eex in E u. But we have also axfex or ax or
means that the middle component is the same. So, remained to
show that: (Rfac , x, Lde ) = (Rfu, x, Lue ) . eaex in E u, ( because
But, (Rfac , x, Lde ) W , means that it exists x V(x ) such xfex = x and e E u ) hence eexea or eea in E u or
that: ufac = xx and deu = xx or fac = fxx and Re = Rea in E u. Equally, we have Lf = Lbf in u E . So,
de = xxe. On the other hand xx E(S) = u E u Eu (Re , x, Lf)2 = (Rea, xfex, Lbf) = (Re , x, Lf) that means
and (Re , x, Lf) E(W) and consequently:
{(Re , x, Lf)| LfRe V(x) and x2 = x} E(W), that proves:
xx E(S) = u E u E u , hence:
xx = ( xxx )x = (xx)(xx ) and E(W) = {(Re , x, Lf)| LfRe V(x) and x2 = x}
xx = (xxx)x = (xx )(xx ) (III) Lets show that:
from which follows xx xx in E u, and since fu E u we E(W ) {(Re, x, Lf ) W | x2 x}
have fuxx fuxx or fufu fac or fu fac. So, Rfu = Rfac
If (Rk , z, Lp ) E(W) , then this element would be product
in E u . In the same way we can show that: Lue = Lde in u E .
Thus we have: of idempotents in E (W ) . But if (Re , x, Lf) and (Rg, y, Lh) are
(Rfu, x, Lue )(Re , x, Lf)(Rfu, x, Lue ) = (Rfac , xxbex, Lde ) = two idempotents in W then, as we showed above , will have
=(Rfu, x, Lue ) (**) x2 = x and y2 = y, moreover
The equalities (*) and (**) indicate that any element (Re , x, Lf) (Rg, y, Lh) ==(Rea, xfgy, Lbh) and
(Re , x, Lf) W has an inverse in W that is (Rfu, x, Lue ), where xE(S), yE(S), while fg uE Eu uEu E(S ) . So,
x V(x). So, W = W( E , S) is regular semigroup. x, y, fg E(S) and since S is orthodox, it follows that xfgy is
idempotent in S. This shows that for every element (Rk , z, Lp)
(II) Lets show now that:
E(W) = {(Re , x, Lf)W | LfRe V(x) and x2 = x} in E (W ) , the middle component z, will be again an
Assume that (Re , x, Lf) is an idempotent of W. So idempotent in S, i.e.
(Re , x, Lf)(Re , x, Lf) = (Re , x, Lf) z E(S). So, (Rk , z, Lp) {(Re , x, Lf) W | x2 = x}, hence we
or
(Rea, xfex, Lbf) = (Re , x, Lf) have: E(W ) {(Re, x, Lf ) W | x2 x}
that means Rea = Re , xfex = x and Lbf = Lf where
While, if (Re , x, Lf)W and x2 = x then (Re , x, Lx ), (Rx , x, Lf) are
a, b E(S ) uEu , such that axfexb or axb in S. idempotents of W. Indeed, to show that (Re , x, Lx ) is
But, idempotent in W, is suffice to show that x2 = x and
ue = xx eue exx e = exx and

## 123906-8585- IJBAS-IJENS @ December 2012 IJENS IJENS

International Journal of Basic & Applied Sciences IJBAS-IJENS Vol:12 No:06 51

## Lx Re V(x). Since the equality x2 = x is true, it remains to Lf) W it follows ue = xxx ue x e ex in Eu

prove that Lx Re V(x). Let be abLx Re where aLx and
bRe . So, La = Lx and Rb = Re , hence (Rb, x, La) = (Re , x, Lx ) where

From (Rb, x, La) W and x2 = x, it follows ub = xx and x V(x) ( because ue, x E u ). Also, (Reac , x, Ldf) W
au = xx for some xV(x), and so we have: ubx = x and
xau = x or xbx = x and xax = x, because u is identity ueac = xxx ueac x eac ex in E u where
element of the semigroup S, i.e. ux = xu = x. We see also that
x V(x) . So,
from La = Lx it follows a x in u E , so there exists t u E
such that a = tx or ax = txx = tx2 = tx = a . So, ax = a or
e ex eac in E u or Reac = Re in E u. Equally, we have
xax = xa or x = xa .
Now we have:
abxab = ab(xa)b = abxb = (ax)bxb = also Ldf = Lf, confirming the fact that u (Ru , u, Lf ) is
= a(xbx)b = axb = (ax)b = ab and
medial idempotent in W.
xabx = (xa)bx = xbx = x
Hence, ab V(x) that means Lx Re V(x). We have shown (V) Finally it remains to show that E E (W ) and
that (Re , x, Lx ) E(W). Similarly we have (Rx , x, Lf) E(W). On
u W u S
the other hand we have:
Let be : E E (W ) such that (x) = (Rxu, uxu, Lux)
(Re , x, Lx )(Rx , x, Lf) = (Rea, xxxx, Lbf) = (Rea, x, Lbf)
where a x b and ue = xx or e = exx. Also, from We see that (Rxu, uxu, Lux ) E (W ) , because
(Rea, x, Lbf) W it follows that there exists x V(x) such uxu uEu = E(S) i.e. (uxu)2 = uxu.
that uea = xx or ea = exx. But, since xx xx in Eu The function is well defined because x E , image (x)
is unique. First, we will show that this function is injective. Let
and e E u it follows exx exx or e ea, i.e. Re = Rea in
x,y E , such that (x) = (y), which means
E u. Equally, we have also Lbf = Lf, that means:
(Re , x, Lf) = (Rea, x, Lbf) or (Re , x, Lf) = (Re , x, Lx ) (Rx , x, Lf) (Rxu, uxu, Lux ) = (Ryu, uyu, Luy ). So, uxu = uyu, xu yu in
hence, every element (Re ,x,Lf) in E u and ux uy in u E . Hence it exists t E u and
2
{(Re , x, Lf ) W | x x} is a production of
g u E such that:
idempotents of E(W) and so: xu = yut and ux = gyu
{(Re , x, Lf ) W | x 2 x } E (W ) x = yutx and x = xguy
Thus, we have shown: uxu = u.yutx.u and uxu = u.xguy.u
uyu = uyutxu and uyu = uxguyu
E(W ) {(Re, x, Lf ) W | x2 x} y = yutx.uy and y = yu.xguy
y = xuy and y = yux.
(IV) Now, we must prove that u (Ru , u, Lu ) is medial Equally we find x = yux and x = xuy showing that x = y. So,
idempotent in W. the function is injektiv. Second, if (Re , x, Lf) is an element
Let (Re , x, Lf) be an element of E (W ) . We have: of E (W ) , we must show that there exists an element of E ,
(Re , x, Lf)(Ru, u, Lu)(Re , x, Lf) = (Rea, xfuu, Lbu)(Re , x, Lf) = such that, its image under is (Re , x, Lf). Since
=(Rea, xxx, Lbu)(Re , x, Lf) = (Rea, x, Lbu) (Re , x, Lf) = (Re , x, Lf) E (W ) , we have x2 = x E(S) and there exists

=(Reac , xbuex, Ldf) = (Reac , xbxxx, Ldf) = (Reac , xbx, Ldf) where xV(x) such that ue = xx and fu = xx. Also the element exf

a x b and c xbx d in S and a, b, c, d E(S). By the belongs to E , because e,x,f E and E is semigroup. Now
let show that (exf) = (Re , x, Lf). Indeed,
definition of W, and since (Rea, x, Lbu) W it follows (exf) = (Rexfu, uexfu, Luexf), and uexfu = xxxxx = xxx = x But
ue = xx and x xx in E u, from which it follows that xue
bu u = xx for some inverse x of x, hence:
in E u. Since is left congruence in E u and e E u, we
bu u = xx bu = xx b = xx xbx = xxxx = xx = x. So,
have ex e or Re = Rex in E u. But Rexfu = Rexxx = Rex
aiming to prove the equality: (Reac , xbx, Ldf) = (Re , x, Lf), we
hence Rexfu = Re in E u and equally we show Luexf = Lf in
have shown xbx = x. Moreover by definition of W, and (Re , x,
u E that means:

## 123906-8585- IJBAS-IJENS @ December 2012 IJENS IJENS

International Journal of Basic & Applied Sciences IJBAS-IJENS Vol:12 No:06 52

(Rexfu, uexfu, Luexf) = (Re, x, Lf) or (exf) = (Re, x, Lf) (xy) = (R(xy)(xy), xy, L(xy)(xy )), it remains to show that
So is surjective. Rxxa = R(xy)(xy) and Ldyy = L(xy)(xy ) . From (Rxxa, xy, Ldyy ) W it
Now let show that is an homomorphism. Let be x,y E follows uxxa = (xy)(xy) or xxa = (xy)(xy) because u is
and let show that: (xy) = (x) (y) or identity element of S and (xy) V(xy). So we have
(Rxyu, uxyu, Luxy ) = (Rux, uxu, Lux ) (Ryu, uyu , Luy ) or Rxxa = R(xy)(xy) and equally Ldyy = L(xy)(xy ). Thus we have
(Rxyu, uxyu, Luxy ) = (Rxua, uxu.ux.yu.uyu, Lbuy ),
Where auxuuxyuuyub and a,bE(S). The middle proved: (xy) = (x) (y) that means u W u S
components are equal, because:
uxu uxyu uyu = uxuxyuyu = uxyu III. CONCLUSION
So, we must show that (Rxyu, uxyu, Luxy ) = (Rxua, uxyu, Lbuy ) or In this paper we have shown that every regular semigroup S
Rxyu, uxyu, Luxy ) = (Rxa, uxyu, Lby ). Thus,it remains to show that containing a medial idempotent u, can constructed using the
Rxyu= Rxa and Luxy = Lby . But (Rxyu, uxyu, Luxy ) W, which subsemigroup of S generated by the set of idempotents

means xyu = (uxyu) (uxyu) where (uxyu) V(uxyu) and E E (S ) and the orthodox subsemigroup of S with identity,
uSu . In the future I will try to do the same construction for
(uxyu) (uxyu) uxyu in E u. So, xyu uxyu in E u. Also,
another class of abundant semigroups, that are quasi-adequate
since (Rxa, uxyu, Lby ) W we have xa uxyu in E u, from semigroups.
REFERENCES
which it follows that xyuxa in E u or Rxyu= Rxa in E u. Its [1] Blyth , T . S and R. B. McFadden , On the construction of a class
the same to show that Luxy = Lby in u E . So, we conclude that of regular semigroups, J. Algebra, 81 (1983), 1 -22.
[2] Blyth , T . S and R. B. McFadden, Naturally ordered regular
(xy) = (x) (y) that means E E (W ) . semigroups with a greatest idempotent. Proc. Roy. Soc. Edinburgh
91 A (1981), 107-122.
Now let be : S u W u such that (x) = (Rxx, x, Lxx ) [3] J. M. Howie, An introduction to semigroup theori.
where xV(x). First, we must show that [4] M. Loganathan, S. Forum 36 (1987), 69 -74. Regular semigroups
with a medial idempotent.
(Rxx, x, Lxx ) u W u . Indeed, if (Re,x,Lf) W, then:
u (Re, x, Lf ) u = (Ru, u, Lu) (Re, x, Lf) (Ru, u, Lu) =
=(Rua, uuex, Lbf) (Ru, u, Lu) = (Ra, uex, Lbf) (Ru, u, Lu)
where ue = xx and fu = xx for some xV(x), so we have:

## u (Re, x, Lf) u = (Ra, xxx, Lbf) (Ru, u, Lu) =

= (Ra, x, Lbf) (Ru, u, Lu) = (Rac , xbfuu, Ldu) = (Rac , xbfu, Ld) =
= (Rac , xbxx, Ld) where a, b, c, d are idempotents in S such
that axb and cxbfud in S. Then u (Re, x, Lf) u =
(Rac , xbxx, Ld), and, since (Ra, x, Lbf) W it follows bfu =
xx where x V(x) or xbxx = xbfu = xxx = x. So,

## u (Re, x, Lf) u = (Rac, x, Ld), i.e. there exists x* V(x) such

that uac = xx* or ac = xx* and also d = du = x*x . Thus, we
have: u (Re, x, Lf) u = ( Rxx*, x, Lx*x). Now, since for any two
elements x, x* V(x) we have Rxx* = Rxx in E u and
Lx*x = Lxx in u E , then we conclude that each element
u (Re, x, Lf) u u W u is of the form ( Rxx, x, Lxx) where
Rxx and Lxx do not depend on the choice of x in V(x). From
what we said, comes immediately that is injective and
surjective function. To show that u W u S we must
prove that is an homomorphism. Let be x,y S, and let
show that (xy) = (x) (y). We see that:
(x) (y) = (Rxx, x, Lxx ) (Ryy, y, Lyy ) =
= (Rxxa, xxxyyy, Ldyy ) = (Rxxa, xy, Ldyy )
where a,bE(S) and a xy d in S. Since